2020
DOI: 10.1097/nnd.0000000000000613
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Comprehensive Preceptor Development Program Through Professional Governance

Abstract: Precepting is a demanding but important role for successful onboarding in healthcare institutions. However, preceptors face many challenges, including inconsistent formal training, selection, and evaluation. One health system took a unique approach to this challenge by developing a transition to practice preceptor program through the institution’s professional governance culture. Program components include clearly outlined selection criteria, formal initial preparation, competency verification, resources, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The average clinical experience of preceptor nurses is approximately 3 years, and they often work as preceptors before becoming competent as nurses [ 6 ]. Preceptor nurses are often overloaded with work and fail to sufficiently educate new nurses because they are required to perform their daily nursing tasks simultaneously [ 7 ]. It was previously reported that the educational effect on new nurses decreased and negatively affected new and preceptor nurses themselves if the preceptor nurses did not have the appropriate competency [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average clinical experience of preceptor nurses is approximately 3 years, and they often work as preceptors before becoming competent as nurses [ 6 ]. Preceptor nurses are often overloaded with work and fail to sufficiently educate new nurses because they are required to perform their daily nursing tasks simultaneously [ 7 ]. It was previously reported that the educational effect on new nurses decreased and negatively affected new and preceptor nurses themselves if the preceptor nurses did not have the appropriate competency [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that the educational effect on new nurses decreased and negatively affected new and preceptor nurses themselves if the preceptor nurses did not have the appropriate competency [ 4 ]. In addition, preceptor nurses often take on the role of preceptors before acquiring the required competency level [ 7 ]. Preceptor nurses feel burdened and stressed in the atmosphere of a nursing organization that appoints the preceptor responsible for all the tasks and responsibilities related to the job of a new nurse [ 8 ] and, thus, tend to avoid the role of the preceptor [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the variability of selection criteria and qualifications, the lack of uniformity of preceptor training programs contributes to mixed outcomes. Several studies reported using preceptor surveys to develop curricular content (Kinsella et al, 2015; Nash & Flowers, 2017; Rogan, 2009), whereas others reviewed the literature (Good, 2021; McKinney & Aguilar, 2020). Preceptor curricula are often not well described, lack a theoretical framework as a basis for practice, and have limited conceptual and pedagogical underpinnings (Trede et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…PTAP acknowledges the importance of an organization having a strong preceptor pool. A well-structured, consistent, and well-developed evidence-based preceptor program may ensure adequate staff preparation and safe, competent patient care (McKinney & Aguilar, 2020). Because of an increased demand for new graduate nurses at one institution, there was the need to provide an opportunity to develop educated and better-prepared preceptors.…”
mentioning
confidence: 99%